Różne modele i przestrzenie unii – przypadek Ukrainy - Bracki, Artur (Tematy i Konteksty, 2019)
The paper is devoted to the analysis of various models and spaces of the Union with reference to Ukraine. The perspective of the religious, political and cultural union was taken as a starting point. Using selected examples and based on the rich literature of the subject, a review of the activities of the Union from the 10th century to the present has been made. An important element of the study was the demarcation of activities unifying inside and outside of one’s own national community. This allowed for more accurate tracing of the mechanisms of community gathering around a particular idea or its rejection. From the reconnaissance it can be concluded that for the Ukrainian space the unification activities were the most favorable, which was marked by the centripetal, convergent and ukrainocentric vector.